2018
DOI: 10.1073/pnas.1718316115
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution cryo-EM structures of actin-bound myosin states reveal the mechanism of myosin force sensing

Abstract: Myosins adjust their power outputs in response to mechanical loads in an isoform-dependent manner, resulting in their ability to dynamically adapt to a range of motile challenges. Here, we reveal the structural basis for force-sensing based on near-atomic resolution structures of one rigor and two ADP-bound states of myosin-IB (myo1b) bound to actin, determined by cryo-electron microscopy. The two ADP-bound states are separated by a 25° rotation of the lever. The lever of the first ADP state is rotated toward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
211
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(242 citation statements)
references
References 42 publications
28
211
3
Order By: Relevance
“…slowing the detachment rate at higher loads to increase the time myosin is attached to actin). The structural mechanism of myosin mechanosensitivity has been investigated in recent studies using X-ray crystallography and cryo-EM, which demonstrated different conformations of the lever arm in nucleotide states that are thought to play a crucial role in mediating force production (35)(36)(37)(38). The two converter mutants we investigated in the current study demonstrated little difference in unloaded sliding velocity but displayed increased sensitivity to external loads examined with load-dependent mixed motor motility assays (Fig.…”
Section: Impact On Mechanosensitivitymentioning
confidence: 67%
See 1 more Smart Citation
“…slowing the detachment rate at higher loads to increase the time myosin is attached to actin). The structural mechanism of myosin mechanosensitivity has been investigated in recent studies using X-ray crystallography and cryo-EM, which demonstrated different conformations of the lever arm in nucleotide states that are thought to play a crucial role in mediating force production (35)(36)(37)(38). The two converter mutants we investigated in the current study demonstrated little difference in unloaded sliding velocity but displayed increased sensitivity to external loads examined with load-dependent mixed motor motility assays (Fig.…”
Section: Impact On Mechanosensitivitymentioning
confidence: 67%
“…There is a second power stroke that occurs during the transition between actomyosin. ADP states, which was identified in structural studies of smooth muscle myosin, myosin V, and myosin IB (35,38,53). Kinetic simulations demonstrate that the power stroke and phosphate release transients are best fit by a fast power stroke (k ϩPWF ) followed by rapid phosphate release (k ϩPi ) ( Figs.…”
Section: Impact Of Converter Mutations On the Power Strokementioning
confidence: 93%
“…Of particular interest is myosin, which binds in a cleft between two actin subunits along the long‐pitch helix of the actin filament, within contact distance to the N‐termini of both actin subunits. The figure shows the recently determined cryo‐EM structure of ADP‐myosin‐IB bound to the actin filament (Mentes et al, ) [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Actin N‐terminal Acetylationmentioning
confidence: 99%
“…Analysis by cryo‐electron microscopy of Myo1b shows that this protein has two binding states to ADP, separated by a 25° lever arm; the first ADP state is important to open the nucleotide‐binding site, the second state allows the stabilization of myosin with F‐actin. In accordance with this information, conformational changes in myosin superfamily are regulated by rotation of the lever arm that affects their association with filamentous actin …”
Section: Class I Myosinsmentioning
confidence: 67%